2009
DOI: 10.1111/j.1439-0434.2008.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Phytophthora infestans Isolates from China

Abstract: A total of 288 (202 from potato and 86 from tomato) isolates of Phytophthora infestans were collected from 1998 to 2007 in China. The isolates were characterized based on mating type, in vitro metalaxyl sensitivity, virulence on potato differentials, allozymes of glucose-6-phosphate isomerase (Gpi), peptidase (Pep), and mitochondrial DNA (mtDNA) haplotype and examined by DNA-based simple sequence repeat (SSR) and random amplified polymorphic DNA (RAPD) fingerprinting. The majority (283 of 288) of the isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Li et al. () used 14 SSR markers to detect the diversity among 60 P. infestans isolates from China, but genotypes of these isolates were not documented and reference isolates were not reported in that study. Guo et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Li et al. () used 14 SSR markers to detect the diversity among 60 P. infestans isolates from China, but genotypes of these isolates were not documented and reference isolates were not reported in that study. Guo et al.…”
Section: Discussionmentioning
confidence: 95%
“…; Li et al. ; Zhu et al. ), few studies have genotyped P. infestans populations with SSR markers, or investigated the possibility of sexual reproduction in the field in North Central China.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower frequencies were observed in other studies, e.g. Nepal 30 out of 251, Estonia 86/432, Finland 66/269, Norway 38/105, Nordic countries (Denmark, Finland, Norway and Sweden) 31/177 and China 61/125 races (Hermansen et al ., ; Ghimire et al ., ; Lehtinen et al ., ; Li et al ., ; Runno‐Paurson et al ., ). It should be noted that in Denmark, Estonia, Finland, Norway and Sweden sexual populations are dominant, and the populations seems to be clonal in China and Nepal (although both mating types can be found), whereas the population in Ecuador is clonal.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study (Zhang et al ., ), the frequency of the A2 mating type was much higher in northern China (Inner Mongolia and Hebei) than in southern China (Sichuan and Yunnan). However, in this study, no A2 isolates were found in northern China, corroborating the reported decline of the A2 mating type in China (Li et al ., ) and the absence of the A2 mating type in northern China (Guo et al ., ). Although the presence of both mating types was observed by Zhang et al .…”
Section: Discussionmentioning
confidence: 99%